Sleepiness and sleepiness perception in patients with Parkinson's disease: a clinical and electrophysiological study. Issue 4 (12th January 2019) - Bargiotas, Panagiotis; Lachenmayer, M Lenard; Schreier, David R; Mathis, Johannes; Bassetti, Claudio L
Abstract: Study Objectives: The main objective of the study was to assess the prevalence, the severity, and the daytime course of excessive daytime sleepiness (EDS) in advanced Parkinson's disease (PD) and to explore how people with PD perceive the degree and onset of their sleepiness during objective sleepiness tests. In addition, the occurrence of early-onset rapid eye movement (REM) periods (sleep-onset REM periods [SOREMPs]) in PD was assessed. Methods: We analyzed data from 46 people with PD (26 males, mean age 63.5 years, mean UPDRS-III-OFF 34.7). The sleep–wake assessment included Epworth sleepiness scale (ESS), Karolinska sleepiness scale (KSS), and objective (polysomnography, multiple sleep latency test [MSLT], and maintenance of wakefulness tests [MWT]) measures. Results: Subjective (ESS ≥ 10) and objective (mean sleep latency, MSL < 5 min in MSLT) EDS were present in 43% and 41% of patients, respectively. The MSL in MSLT and MWT remained unchanged throughout the day and significantly correlated with KSS during the trial but not with KSS shortly before it. In MWT, about one-fourth of patients failed to signal their sleepiness before falling asleep. SOREMPs, usually (83%) arising from NREM1 or wake, were recorded in 24% of the patients. People with SOREMPs had significantly lower MSL in MSLT and MWT and higher AHI compared with those without SOREMPs. Conclusions: Patients with PD exhibit daylong increased EDS but they underestimate its degree and often fail to signal its onset. SOREMPs in PD have a "narcoleptic" character in sleep-stage sequencing and are associated with the presence of sleep-disturbed breathing. These results add to our understanding of sleepiness and sleepiness perception in PD and have important implications for its diagnosis and management.